2022
DOI: 10.1126/sciadv.abq5058
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase 4 disruption decreases synaptic and behavioral adaptations induced by cocaine withdrawal

Abstract: Cocaine use followed by withdrawal induces synaptic changes in nucleus accumbens (NAc), which are thought to underlie subsequent drug-seeking behaviors and relapse. Previous studies suggest that cocaine-induced synaptic changes depend on acid-sensing ion channels (ASICs). Here, we investigated potential involvement of carbonic anhydrase 4 (CA4), an extracellular pH-buffering enzyme. We examined effects of CA4 in mice on ASIC-mediated synaptic transmission in medium spiny neurons (MSNs) in NAc, as well as on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Because NAcc is thought to be an important site of ASIC action in cocaine seeking ( Kreple et al, 2014 ; Gupta et al, 2022 ), we assessed expression of ASIC2A and ASIC2B subunits at this site. We dissected out NAcc bilaterally from wild-type and Asic2 −/− mice and assessed ASIC2 expression via western blot.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because NAcc is thought to be an important site of ASIC action in cocaine seeking ( Kreple et al, 2014 ; Gupta et al, 2022 ), we assessed expression of ASIC2A and ASIC2B subunits at this site. We dissected out NAcc bilaterally from wild-type and Asic2 −/− mice and assessed ASIC2 expression via western blot.…”
Section: Resultsmentioning
confidence: 99%
“…A number of previous studies have also reported effects of cocaine withdrawal on spines in NAcc MSNs, however results of these studies have varied. While some have reported increased dendritic spines in NAcc following cocaine withdrawal ( Christian et al, 2017 ; Gupta et al, 2022 ), others have reported decreased spine density ( Dumitriu et al, 2012 ). Some have reported effects only in specific populations of MSNs, stratified by presynaptic input or dopamine receptor (D1R/D2R) classification ( Lee et al, 2006 ; Kim et al, 2011 ; MacAskill et al, 2014 ; Siemsen et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations